Pelatihan Peningkatan Kemampuan Bahasa Inggris melalui Media Games di Lingkup Komunitas Ternate - Sulmi Magfirah; Sutisno Adam; Farida Maricar; Indra Purnawan Pandjaitan (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
The community service activities by Unkhair team in the form of English language skills training in Ternate communities aims to increase the enthusiasm of community members to learn English and improve English skills through effective, creative and fun learning, in this case through media games. The method used prioritizes courage in speaking without worrying about being wrong in pronunciation or expression in using English. The sample are around 40 participants by the community members in Ternate. Games are used as English communication media between mentor and participants. Finally, the result of this activity is the increase of English ability of the participants in using games, therefore the learning process is more effectice, creative, and fun.